Australian Representatives to the UNWCC, 1943–1948 - Morris, Narrelle (2022)
Australia had a number of significant personnel involved in the United Nations War Crimes Commission (UNWCC). Yet the strongest Australian influence on the UNWCC was not Australian at all; it was the British-born jurist Lord Wright of Durley, who served as Australia’s representative from mid-1944 and as UNWCC chair during the pivotal years from 1945 to 1948. Lord Wright took charge only months before the wars in Europe and the Pacific ended and thus played a significant role in directing the UNWCC’s efforts during this crucial period. Unfortunately, the UNWCC became less and less able over time to influence its national members and their approaches to prosecuting war crimes. The eventual sidelining of the UNWCC does not, however, change its important place in the history of multilateral institutions that sought to deal with war crimes committed in the twentieth century by means of international criminal law. Nor does it detract from the honest and industrious work of the various national representatives, including Lord Wright, to ensure that war criminals did not escape justice.